A qualitative study of emergency and intensive care unit nurses’ experience of workflow: I enjoy the “flow” at work - Yuchen Liu; Danli Zheng; Yaru Xiao; Ying Li; Sufang Huang; Jie Xiong (BMC Nursing)
Abstract Objective This study aims to investigate the workflow experiences of nurses in Emergency Departments (EDs) and Intensive Care Units (ICUs), with the goal of providing a theoretical and practical foundation for enhancing nursing care quality, service levels, and occupational satisfaction among nursing staff. Methods A descriptive qualitative research design was adopted to explore the workflow experiences of nurses in EDs and ICUs. Participants included 22 nurses recruited from a tertiary hospital in Wuhan, China, between September and November 2024. Data were collected through semi-structured interviews conducted in three rounds (12 participants in the first round, 6 in the second, and 4 in the third), with a two-week interval between each round to ensure methodological rigor, data depth, and consistency. Thematic analysis was employed for data processing, which involved systematic coding, theme extraction, and categorization to identify key themes and subthemes aligned with the research objectives. Results The analysis revealed three overarching themes and nine subthemes: (1) Triggers for workflow experiences (Triggering, Self-Regulation), (2) Influencing factors of workflow experience (Nursing Skills and Work Experience, Working Relationships, and Teamwork Patterns), and (3) Positive effects of workflow experience (Quality of Nursing Care and Service Level, Career Development, Job Satisfaction, and Positive Carryover Effect). Conclusion To promote the Flow experience among nurses in EDs and ICUs, nursing managers should prioritize the creation of a supportive work environment and implement strategies to enhance nurses’ self-regulation skills. These measures are essential for optimizing workflow experiences, improving patient care outcomes, and fostering professional satisfaction among nursing staff. Clinical trial number Not applicable.